Magnetic Storm‐Time Red Aurora as Seen From Hokkaido, Japan on 1 December 2023 Associated With High‐Density Solar Wind - Ryuho Kataoka; Yoshizumi Miyoshi; Kazuo Shiokawa; Nozomu Nishitani; Kunihiro Keika; Takanobu Amano; Kanako Seki (Geophysical Research Letters)
Abstract We report a citizen science‐motivated study on the cause of an unusually bright red aurora as witnessed from Hokkaido, Japan during a magnetic storm on 1 December 2023. The auroral brightness of 5 kR is unusual for the Dst index peak of only −107 nT. In spite of the moderate storm amplitude, the extremely high solar wind density of >50/cc and dynamic pressure of >25 nPa caused the aurora oval extension to 53 magnetic latitudes (L = 2.8). We discuss that the drift loss of the ring current particles across the small‐size magnetopause is important, and Hokkaido was at the right position to see the direct effect of the large particle injection of the storm‐time substorm.